High volume training recommended for athletes with uncomplicated pregnancies - Dixon, S. (SIRC Newsletter, 2008)
Background Previous studies have concluded that moderate exercise has no adverse effects during uncomplicated pregnancy. For women who are well-trained prior to pregnancy, more vigorous exercise has also been shown to be safe.